PROCESSING OBJECT SOUNDS, AN EXPLORATION OF SAMPLING IN DIGITAL MUSIC - Wijaya, Gabrielle; Dinata, Komang Wahyu (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
The practice of sampling-capturing, manipulating, and recontextualizing sounds from the physical world-has become the cornerstone of digital music production. Among the diverse ranges of sampled sounds, object sounds-auditory impressions derived from everyday items and environments-offer unique creative possibilities. This study explores the process of incorporating object sounds into digital music, examining how they can be recorded, manipulated, and transformed through various digital tools and techniques. The ability to sample objects provides musicians and sound designers with a rich palette to create unconventional textures, rhythms, and sonic landscapes. Additionally, this exploration delves into the psychological and emotional impact of object-based sounds on listeners, considering how they evoke memories, sensations, or associations. By investigating the intersection of field recording, digital processing, and music composition, this study underscores the artistic potential of object sounds in shaping the future of experimental and mainstream music production. As digital tools evolve, the role of object sounds continues to expand, thereby encouraging new forms of auditory expressions and interactivity in the music industry.